1989
DOI: 10.1071/ch9891727
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Australian Soft Corals. XLVII. New Halogenated Briaran Diterpenes From a Briareum Species (Octocorallia, Gorgonacea)

Abstract: Two new halogenated briaran diterpenes (3) and (4) are reported from a Briareumspecies of soft corals from waters off Darwin, N.T. Their structures were determined by high-field n.m.r. spectroscopy including 2-D 13C-1 H-correlation experiments and COSY-45 experiments, and stereochemical features were delineated by n.0.e. difference spectroscopy. The new metabolites are (1R*,2S*,4S*,6S*,7R',8R*,9S*,10S*,11Z,14S*,17S*)-14-acetoxy-6-chloro-4,8-epoxy-9,17-dihydroxy-2-propiony10xybriar5(16,11-dien-18-one (3) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
14
0

Year Published

1991
1991
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…Briaran diterpenes continue to attract the attention of investigators because of the structural complexity and interesting bioactivity (e.g., cytotoxicity, ,, antiinflammatory, ,, antiviral, , insecticidal 3 ) associated with several compounds of this type. The genus Briareum has been found to be situated near the transition between the Gorgonacea and Alcyonacea, both in chemical and taxonomic terms. , Previous studies have shown that species identification could be assisted by investigation of secondary metabolites from organisms of the Briareum sp. ,, In connection with our continuing studies of bioactive secondary metabolites from marine organisms, the chemistry of a specimen of Briareum sp., originally identified as Pachyclavularia violacea on the basis of similarity in colonial morphology, was studied. The specimen identification was subsequently revised on the basis of its chemical constituents.…”
supporting
confidence: 77%
See 1 more Smart Citation
“…Briaran diterpenes continue to attract the attention of investigators because of the structural complexity and interesting bioactivity (e.g., cytotoxicity, ,, antiinflammatory, ,, antiviral, , insecticidal 3 ) associated with several compounds of this type. The genus Briareum has been found to be situated near the transition between the Gorgonacea and Alcyonacea, both in chemical and taxonomic terms. , Previous studies have shown that species identification could be assisted by investigation of secondary metabolites from organisms of the Briareum sp. ,, In connection with our continuing studies of bioactive secondary metabolites from marine organisms, the chemistry of a specimen of Briareum sp., originally identified as Pachyclavularia violacea on the basis of similarity in colonial morphology, was studied. The specimen identification was subsequently revised on the basis of its chemical constituents.…”
supporting
confidence: 77%
“…Gorgonians (order Gorgonacea) and soft corals (Alcyonacea) are known to be important sources of diterpenoids in the marine environment. The gorgonacean genus Briareum has been the subject of many investigations that have led to the discovery of oxygenated diterpenes, including briareins, asbestinins, cladiellins, and cembranes . Briaran diterpenes continue to attract the attention of investigators because of the structural complexity and interesting bioactivity (e.g., cytotoxicity, ,, antiinflammatory, ,, antiviral, , insecticidal 3 ) associated with several compounds of this type.…”
mentioning
confidence: 99%
“…Compound 7 can be assigned nearly the same conformation as found for 4-6 since the H-15 resonance is downfield (1.55 ppm) as in the latter set of compounds and the H-14/H-13 coupling is large indicating a 14-axial (and ß) hydrogen orientation. The epoxide on the lactone ring is assigned an a orientation by virtue of the nOe between H-l 8 and H-9 and correspondence of the 13C-nmr resonances for C-8 and C-17 in the group of diterpenes reported here and related compounds (1,3,4,12).…”
mentioning
confidence: 53%
“…[1] Among them, halogenated compounds Ϫ predominantly steroids, [2] diterpenes, [3] alkaloids, [4] and prostanoids [5] Ϫ have received much attention because of their strong antiinflammatory and antitumor activities. The chemistry of prostaglandins has now entered a new stage, thanks to newly discovered, predominantly halogenated, compounds.…”
Section: Introductionmentioning
confidence: 99%